Contrast-Enhanced Ultrasound of Primary Squamous Cell Carcinoma of the Thyroid: A Case Report - Chen, Sijie; Peng, Qinghai; Zhang, Qi; Niu, Chengcheng (Frontiers in Endocrinology, 2020)
Introduction: Primary squamous cell carcinoma of the thyroid (ThyPSCC) is an extremely rare aggressive malignancy with a poor prognosis. However, almost no report thus far has investigated the microvasculature of ThyPSCC imaged using contrast-enhanced ultrasound (CEUS). Case report: A 59-year-old male patient presented to our hospital with progressively worsening hoarse voice symptoms for 20 days and was diagnosed with left unilateral vocal fold palsy. Ultrasonography revealed a solitary marked hypoechoic thyroid nodule with an unclear boundary in the inferior part of the left lobe. Color Doppler flow imaging (CDFI) showed a poor blood flow signal inside this nodule. CEUS images showed a persistent low peak enhancement of the nodule from its periphery to its center. The time-intensity curve (TIC) displayed a wash-in time of 10 s, a time to peak of 37 s, a peak signal intensity of 24.5% and a wash-out time of 70 s for the thyroid tumor. Finally, left hemithyroidectomy of the thyroid tumor was performed, and histopathologic and immunohistochemical (IHC) evaluations confirmed the diagnosis of ThyPSCC. Postoperatively, the patient received a combination therapy of chemotherapy, radiotherapy and targeted therapy, but the patient died 4 months after surgery. Conclusion: ThyPSCC is a rare but aggressive malignancy of the thyroid. Herein, we reported a case of ThyPSCC and its ultrasonography and pathologic findings.